Research Network of Tehran Defined Population: Methodology and Establishment - Ali-Asghar Kolahi; Ahmad-Reza Farsar; Shahnam Arshi; Mortaza Abdollahi; Alireza Abadi (Shahid Beheshti University of Medical Sciences, 2015)
Background: We need a defined population for determining prevalence and incidence of diseases, as well as conducting interventional, cohort and longitudinal studies, calculating correct and timely public health indicators, assessing actual health needs of community, performing educational programs and interventions to promote healthy lifestyle, and enhancing quality of primary health services. The objective of this project was to determine a defined population which is representative of Tehran, the Capital of Iran. This article reports the methodology and establishment of the research network of Tehran defined population. Methods: This project started by selecting two urban health centers from each of the five district health centers affiliated to Shahid Beheshti University of Medical Sciences in 2012. Inside each selected urban health center, one defined population research station was established. Two new centers have been added during 2013 and 2014. For the time being, the number of the covered population of the network has reached 40000 individuals. The most important criterion for the defined population has been to be representative of the population of Tehran. For this, we selected two urban health centers from 12 of 22 municipality districts and from each of the five different socioeconomic of Greater Tehran. Merely 80000 individuals in neighborhoods of each defined population research station were considered as control group of the project. Findings: Totally we selected 12 defined population research stations and their under-covered population developed a defined population which is representative of Tehran population. Conclusion: a population lab is ready now in metropolitan of Tehran.